QRFP43 modulates the activity of the hypothalamic-pituitary-thyroid axis in female sheep - Bartosz Jarosław Przybył; Michał Szlis; Anna Misztal; Anna Wójcik-Gładysz (Scientific Reports)
Abstract Since the early discovery of QRFP43, intensive research has been primarily focused on its role in the modulation of food intake. As is widely recognised, the regulation of the body’s energy status is a highly complex process involving numerous systems, hormones and neurotransmitters. Among the most important regulators of energy status, alongside the satiety and hunger centre located in the hypothalamus, is the HPT axis, which directly and indirectly affects the regulation of metabolism in all cells of the body. Therefore, it seems highly important to conduct studies aimed at elucidating how QRFP43 may impact the secretory activity of the HPT axis. The objective of this work was to investigate the role of QRFP43 in modulating HPT axis activity in sheep. The study examined mRNA and peptide expression of TRH and TSH in the hypothalamus and pituitary, as well as plasma concentrations of TSH, free T4 (FT4) and free T3 (FT3). Moreover, the relationship between QRFP34 and mRNA expression of the Dio1, Dio2, and Dio3 genes was explored in selected tissues of the HPT axis. The animals (n = 48) were randomly divided into three experimental groups: a control group receiving an ICV infusion of Ringer-Locke solution, and two experimental groups receiving ICV infusions of QRFP43 at doses of 10 and 50 µg per day. Four 50-minute ICV infusions were administered to all sheep at 30 min intervals each of three consecutive days. Hypothalamic, pituitary and thyroid glands were collected and preserved for further immunohistochemical and molecular biological analyses. Additionally, blood samples were collected during the experiment for subsequent RIA determinations. In summary, the results of the experiment have indicated that QRFP43 modulates the secretory activity of the HPT axis at all organisational levels. Moreover, QRFP43 can alter the mRNA expression profiles of DIO1, DIO2 and DIO3 in HPT tissues, leading to discrete changes in the metabolism of the cells studied and their response to signals transmitted by T4 and T3.